2005
DOI: 10.1111/j.1744-7410.2005.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the female reproductive system in Hippolyte inermis (Decapoda, Caridea): is this species really hermaphroditic?

Abstract: Abstract. The majority of the published data about the reproductive biology of the decapod shrimp, Hippolyte inermis support the idea that this species is a protandric hermaphrodite, as is reported to be the case for certain other caridean species. However, our studies, based on the relative growth of the male reproductive appendage and histological examinations of the ovary, testes, oviducts, and deferentia vasa, indicate that there is no evidence supporting the occurrence of protandry. The first report of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
5
18
0
1
Order By: Relevance
“…Finally, these results (based on 176 males studied without any signs of sex reversal), altogether with our previous studies (Cobos et al 2005;Manjón-Cabeza et al 2009), support the existence of a gonochoric structure of the studied population of H. inermis (from Zostera beds) like has been described recently in other species of the same genus such as H. williamsi Schmitt 1924 H. obliquimanus Dana 1852 (Espinoza-Fuenzalida et al 2008;Terossi et al 2008).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, these results (based on 176 males studied without any signs of sex reversal), altogether with our previous studies (Cobos et al 2005;Manjón-Cabeza et al 2009), support the existence of a gonochoric structure of the studied population of H. inermis (from Zostera beds) like has been described recently in other species of the same genus such as H. williamsi Schmitt 1924 H. obliquimanus Dana 1852 (Espinoza-Fuenzalida et al 2008;Terossi et al 2008).…”
Section: Discussionsupporting
confidence: 66%
“…However, two different studies from our laboratory have found no evidence for hermaphroditic sexuality in adult specimens of this species after a careful examination of the morphology of the reproductive structures (Cobos et al 2005) and an exhaustive study of its population structure and absolute growth (Manjón-Cabeza et al 2009). Recent studies regarding the reproductive system in other species of Hippolyte have not found either any cases of sex reversal (Espinoza-Fuenzalida et al 2008;Terossi et al 2008), and consequently they were described as gonochoristic species.…”
Section: Introductionmentioning
confidence: 99%
“…Also, laboratory experiments demonstrated that males might live and grow steadily for months before dying without experiencing any morphological change that might denote sex change. All this information represents strong evidence that the studied species is not a hermaphrodite but a gonochorist in contrast to that reported for other congeners (Zupo and Messina 2007; but see Cobos et al 2005).…”
Section: Discussionmentioning
confidence: 53%
“…However, preliminary observations indicated that males were smaller than females. Although this size diVerence between the sexes is suggestive of protandry, as reported for its congener Hippolyte inermis (Zupo and Messina 2007; but see Cobos et al 2005), gonochorism cannot be ruled out as an alternative pattern of gender expression (see Terossi et al 2008). To properly examine the sexual system of H. williamsi, we sampled in diVerent seasons to document the population structure and sexual characters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation